Undermatching: The role of familial involvement in college choice among working class students - Martin, Kelley L. (My University, 2020)
The purpose of this qualitative study was to better understand how working-class students and their families make decisions regarding institutional choice specifically around institutional selectivity. By understanding the college-choice process of low-income working-class students, institutions of higher education and practitioners will gain a better understanding of how to recruit and retain high achieving low-income working-class students. Increased enrollment of low-income working-class students at more selective institutions not only assists the college or university in diversifying their student body, but evidence suggests low-income working-class students have better educational outcomes when attending an institution well matched to their level of academic achievement. Through the use of semi-structured interviews, 10 college students and the family member most influential in the student’s college-going decisions were interviewed. There was a total of 19 participants interviewed. Each student were enrolled in their first year at an institution of higher education. The results of the study showed the highly impactful role that high school counselors played in helping students determine which institution to attend. In addition, the results explain how low-income working-class families developed a college-going consciousness in their household. The results explored how families supported and found value in attending an institution of higher education.
Keywords: Education; Student affairs services; College Students